2012
DOI: 10.1590/s1808-86942012000100005
|View full text |Cite
|
Sign up to set email alerts
|

Cochlear implant radiography: technique adapted into a portable apparatus

Abstract: Although the portable X-ray apparatus presents limitations, the employment of proper techniques and accessories makes possible the obtainment of satisfactory radiographies to observe cochlear implants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 2 publications
0
5
0
1
Order By: Relevance
“…While simple to understand, these methods require either a post-insertion computed tomography (CT) scan, which adds radiation, cost and time to the procedure [1-3, 6], or a precisely protocolled skull radiograph that requires expertise of the technician and usually adds an extra postoperative visit for the patient [4, 7, 8]. Additionally, image processing software is needed to calculate angles and distances of the electrode contacts.…”
Section: Introductionmentioning
confidence: 99%
“…While simple to understand, these methods require either a post-insertion computed tomography (CT) scan, which adds radiation, cost and time to the procedure [1-3, 6], or a precisely protocolled skull radiograph that requires expertise of the technician and usually adds an extra postoperative visit for the patient [4, 7, 8]. Additionally, image processing software is needed to calculate angles and distances of the electrode contacts.…”
Section: Introductionmentioning
confidence: 99%
“…Both studies cited the risk of cataracts due to radiation exposure and discussed the potential for the preoperative CT scan and possible multiple intraoperative radiographs culminating in a harmful amount of radiation, especially in the pediatric population. However, the other five studies examining intraoperative X‐ray in this systematic review concluded that intraoperative X‐ray was useful . The rate of electrode misplacement across these studies, 2.2%, is low but not negligible, which is considered to be a major complication because accurate placement is critical for successful auditory rehabilitation .…”
Section: Discussionmentioning
confidence: 88%
“…However, the other five studies examining intraoperative X-ray in this systematic review concluded that intraoperative X-ray was useful. 9,12,[22][23][24] The rate of electrode misplacement across these studies, 2.2%, is low but not negligible, which is considered to be a major complication because accurate placement is critical for successful auditory rehabilitation. 19 Revision surgery in these patients incurs additional cost and may cause increased morbidity.…”
Section: Discussionmentioning
confidence: 91%
“…Similarly, Shpizner et al (32) reported that a Stenvers (45 degrees) and an anterior-posterior projection is sufficient to confirm the electrode placement. Molezini et al (33) described a radiological technique that uses two views with a portable X-ray device. This included anteroposterior (transorbital) and 45-degree oblique views (Stenvers' method).…”
Section: Introductionmentioning
confidence: 99%